Associations of two common genetic variants with breast cancer risk in a chinese population: a stratified interaction analysis. - Yuxiang Lin; Fangmeng Fu; Minyan Chen; Meng Huang; Chuan Wang (PLoS ONE)
Recent genome-wide association studies (GWAS) have identified a series of new genetic susceptibility loci for breast cancer (BC). However, the correlations between these variants and breast cancer are still not clear. In order to explore the role of breast cancer susceptibility variants in a Southeast Chinese population, we genotyped two common SNPs at chromosome 6q25 (rs2046210) and in TOX3 (rs4784227) in a case-control study with a total of 702 breast cancer cases and 794 healthy-controls. In addition, we also evaluated the multiple interactions among genetic variants, risk factors, and tumor subtypes. Associations of genotypes with breast cancer risk was evaluated using multivariate logistic regression to estimate odds ratios (OR) and their 95% confidence intervals (95% CI). The results indicated that both polymorphisms were significantly associated with the risk of breast cancer, with per allele OR = 1.35, (95%CI = 1.17-1.57) for rs2046210 and per allele OR = 1.24 (95%CI = 1.06-1.45) for rs4784227. Furthermore, in subgroup stratified analyses, we observed that the T allele of rs4784227 was significantly associated with elevated OR among postmenopausal populations (OR = 1.44, 95%CI 1.11-1.87) but not in premenopausal populations, with the heterogeneity P value of P = 0.064. These findings suggest that the genetic variants at chromosome 6q25 and in the TOX3 gene may play important roles in breast cancer development in a Chinese population and the underlying biological mechanisms need to be further elucidated.